Author the red-med railway project a serious competitor to the suez canal for cargo containers? - Lakhal, Salem Y. (2017)
Israel and China have finalized a project plan initiated in 2012. This project received the green light from Israeli cabinet in March 2014. With this venture, China will build a cargo railway line connecting the port of Eilat in the Red Sea to the ports of Ashdod and Haifa on the Mediterranean coast in Israel. This project will be a shipping alternative to the Suez Canal. This statement is the corner stone of this paper and considered an hypothesis to be verified within this paper. The methodology used is based on the concept of “market position.” The main conclusion, theoretically, the Red-Med railway could be an alternative to the Suez Canal for in the 4,000 TFE Vessels containers transportation as far as costs are concerned. However, other concerns, such as the security in the Suez Canal and the risk of its shutdown, must be considered too.